2016
DOI: 10.1177/0733464815625833
|View full text |Cite
|
Sign up to set email alerts
|

Translating Strong for Life Into the Community Care Program: Lessons Learned

Abstract: We used a randomized controlled trial to test the implementation of Strong for Life (SFL), a resistance exercise intervention, using 32 home care aides (HCAs) as exercise leaders with their 42 homebound older adult clients enrolled in the Community Care Program, a Medicaid 1915(c) waiver program. Mixed-methods were used to analyze outcomes of program satisfaction rates, training session evaluations, program fidelity, and job descriptive index scores. Results indicate that it is feasible for HCAs to implement S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Clients have pronounced physical limitations and 99% are limited in completing instrumental activities of daily living such as housework, meal preparation, laundy, and activities outside of the home. Our previous work with this population found that 40% of HCAs did not have a high school diploma indicating the low levels of formal education among these formal caregivers (Danilovich, 2016). Based on this demographic profile, our knowledge of client and HCA abilities, and the preferences of clients and HCAs, we worked with the mobile app developers to purposefully create a very simplistic app that would be straightforward for naïve technology users and those without high levels of education.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Clients have pronounced physical limitations and 99% are limited in completing instrumental activities of daily living such as housework, meal preparation, laundy, and activities outside of the home. Our previous work with this population found that 40% of HCAs did not have a high school diploma indicating the low levels of formal education among these formal caregivers (Danilovich, 2016). Based on this demographic profile, our knowledge of client and HCA abilities, and the preferences of clients and HCAs, we worked with the mobile app developers to purposefully create a very simplistic app that would be straightforward for naïve technology users and those without high levels of education.…”
Section: Resultsmentioning
confidence: 89%
“…Both studies showed HCAs could be trained to lead an exercise intervention and implement it successfully during usual care hours. Importantly, intervention satisfaction was high in both studies and 100% of clients and HCAs stated that exercise programs should be offered for all Medicaid HCBS clients (Danilovich, Hughes, Corcos, Marquez, & Eisenstein, 2016). However, Strong for Life was not originally intended for older adults receiving HCBS and Healthy Moves for Aging Well does not follow the ACSM recommendations for resistance exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to recruit 63 HCAs and one of their clients per study arm for a total sample size of 126 HCA-client dyads. In our pilot study of 42 clients, overall attrition was 17% [13] . Allowing for similar attrition, we project 50 subjects per arm with complete data at three- and six-month follow-up.…”
Section: Methodsmentioning
confidence: 83%
“…While it is well established that progressive resistance exercise (PRE) improves muscle strength in both health and disease [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , it is not clear how best to engage frail older adults with limited community access in a PRE intervention [16] . It is also unclear the extent to which PRE can slow or reverse frailty [8] .…”
Section: Introductionmentioning
confidence: 99%